Spine injury assessment under spaceflight landing conditions using multibody model. (December 2018) - Pasha Zanoosi, AA; Kalantarinejad, R; Haghpanahi, M
The novelty of the study relies on the fact that current simulations of human body to assess spine injury are based on finite element method. Spine injury assessment is an important point in designing spacecraft seat especially during landing. The finite element-based human body simulations are very time-consuming and computationally expensive. These problems make it difficult to perform high computational simulations such as optimization, sensitivity analysis, and so forth. Hence, in this study, it is tried to resolve these problems by developing a multibody model of human body in landing phase of spacecraft. This model makes designers able to perform corresponding simulations faster with acceptable accuracy. This study presents a dynamic multibody model of spacecraft seat-occupant system for spine injury assessment under landing conditions. The landing situation of spacecraft exposes shock loads to the spacecraft and astronaut. Hence, spine injury assessment under landing conditions enables optimal injury design of seat-occupant system. The modeling method is based on using the multibody modeling to achieve a detailed description containing the nonlinear properties and the accuracy of a multibody dynamic model considering whole body comprising stretching of vertebrae. The human body model comprises head, spine, femur, and shank lying on a flexible polyurethane foam as seat cushion. To model the spine, viscera, and pelvis in the sagittal plane, the spine column considered to be rigid bodies accompanied by spring-damper elements. To validate the developed model, the modal analysis and seat-to-head transmissibility of the spine has been validated by comparing with previously published models. Finally, as an application, the developed model has been exposed to a landing shock load for spine injury assessment.